Plasmonic nanodiamonds: targeted core-shell type nanoparticles for cancer cell thermoablation - Rehor, Ivan; Lee, Karin L; Chen, Kevin; Hajek, Miroslav; Havlik, Jan; Lokajova, Jana; Masat, Milan; Slegerova, Jitka; Shukla, Sourabh; Heidari, Hamed; Bals, Sara; Steinmetz, Nicole F; et al. (Advanced healthcare materials, 2015)
Targeted biocompatible nanostructures with controlled plasmonic and morphological parameters are promising materials for cancer treatment based on selective thermal ablation of cells. Here, core-shell plasmonic nanodiamonds consisting of a silica-encapsulated diamond nanocrystal coated in a gold shell are designed and synthesized. The architecture of particles is analyzed and confirmed in detail using electron tomography. The particles are biocompatibilized using a PEG polymer terminated with bioorthogonally reactive alkyne groups. Azide-modified transferrin is attached to these particles, and their high colloidal stability and successful targeting to cancer cells overexpressing the transferrin receptor are demonstrated. The particles are nontoxic to the cells and they are readily internalized upon binding to the transferrin receptor. The high plasmonic cross section of the particles in the near-infrared region is utilized to quantitatively ablate the cancer cells with a short, one-minute irradiation by a pulse 750-nm laser.
Keywords: transferin; HeLa Cells; Nanodiamonds; indukovaná hypertermie; Nanoshells; Hyperthermia, Induced; biokompatibilní materiály; Nanoparticles; zlato; Polyethylene Glycols; nanoslupky; cílená molekulární terapie; lidé; HeLa buňky; receptory transferinu; nanodiamanty; Ablation Techniques; Transferrin; nanočástice; Receptors, Transferrin; polyethylenglykoly; Biocompatible Materials; Gold; karbocyaniny; Molecular Targeted Therapy; ablace; laserová terapie; Carbocyanines; Laser Therapy; Humans